Latitudinal variation in arrival and breeding phenology of the pied flycatcher Ficedula hypoleuca using large‐scale citizen science data. (12th February 2021) - Nicolau, Pedro G.; Burgess, Malcolm D.; Marques, Tiago A.; Baillie, Stephen R.; Moran, Nick J.; Leech, Dave I.; Johnston, Alison
Abstract : Many species have advanced the timing of annual reproductive cycles in response to climatic warming, sometimes leading to asynchrony between trophic levels, with negative population consequences. Long‐distance migratory birds, reliant on short seasonal food pulses for breeding, are considered particularly susceptible to such disjunction because late arrival may preclude optimal timing of egg‐laying. It is unknown whether the relative timing of arrival and egg‐laying is sufficiently plastic, in time and space, to enable an adaptive response when arrival times change relative to local food resources. We used citizen science data, describing pied flycatcher Ficedula hypoleuca arrival and egg‐laying dates, to explore temporal (2013–2016) and spatial (across Great Britain) variation in the phenology of arrival, laying and their difference. To assess the long‐term trend in arrival and laying at a single location, we used data from a long‐term field study. The arrival‐laying interval was consistently shorter in the north, driven by the contrast between spatial variation in arrival date and spatial invariance in laying date. To understand whether a short arrival‐laying interval may have consequences for productivity, we assessed the association between this interval and clutch size. We found no statistically significant correlation between these two variables. To examine long‐term changes in arrival and laying dates, we focussed on a single location in southwestern England. Both dates of first male arrival and first egg laid in a season advanced since 1986, with no evidence of interval shortening. Together, our results demonstrate spatial and annual variation in the arrival‐laying interval, with no detected effect on fecundity. Thus, the interval from arrival to laying is likely dictated by spatially and temporally varying local conditions, suggesting these migrant birds may have the ability to adapt this interval to align with local conditions and mitigate potential mismatch impacts.